Defining and Measuring Moral Injury: Rationale, Design, and Preliminary Findings From the Moral Injury Outcome Scale Consortium. Issue 3 (4th April 2019) - Yeterian, Julie D.; Berke, Danielle S.; Carney, Jessica R.; McIntyre‐Smith, Alexandra; St. Cyr, Katherine; King, Lisa; Kline, Nora K.; Phelps, Andrea; Litz, Brett T.
Abstract: In the current paper, we first describe the rationale for and methodology employed by an international research consortium, the Moral Injury Outcome Scale (MIOS) Consortium, the aim of which is to develop and validate a content‐valid measure of moral injury as a multidimensional outcome. The MIOS Consortium comprises researchers and clinicians who work with active duty military service members and veterans in the United States, the United Kingdom, the Netherlands, Australia, and Canada. We describe the multiphase psychometric development process being conducted by the Consortium, which will gather phenomenological data from service members, veterans, and clinicians to operationalize subdomains of impact and to generate content for a new measure of moral injury. Second, to illustrate the methodology being employed by the Consortium in the first phase of measure development, we present a small subset of preliminary results from semistructured interviews and questionnaires conducted with care providers ( N = 26) at three of the 10 study sites. The themes derived from these initial preliminary clinician interviews suggest that exposure to potentially morally injurious events is associated with broad psychological/behavioral, social, and spiritual/existential impacts. The early findings also suggest that the outcomes associated with acts of commission or omission and events involving others' transgressions may overlap. These results will be combined with data derived from other clinicians, service members, and veterans to generate the MIOS. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Definiendo y midiendo el daño moral: fundamentos, diseño y resultados preliminares de la escala consorcio de consecuencias del daño moral DEFINIENDO Y MIDIENDO EL DAÑO MORAL En el documento actual, describimos en primer lugar los fundamentos y la metodología empleados por un consorcio internacional de investigación, la Escala Consorcio de consecuencias del daño moral (MIOS en sus siglas en inglés), cuyo objetivo es desarrollar y validar una medida de daño moral con contenido válido y como consecuencias multidimensionales. El Consorcio MIOS está compuesto por investigadores y clínicos que trabajan con miembros del servicio militar activos y veteranos en los Estados Unidos, el Reino Unido, los Países Bajos, Australia y Canadá. Describimos el proceso de desarrollo psicométrico multifase que está llevando a cabo el Consorcio, que recopilará datos fenomenológicos de miembros del servicio, veteranos y clínicos para poner en práctica subdominios de impacto y generar contenido para una nueva medida de daño moral. En segundo lugar, para ilustrar la metodología empleada por el Consorcio en la primera fase de desarrollo de la medida, presentamos un pequeño subconjunto de resultados preliminares de entrevistas semiestructuradas y cuestionarios realizados con proveedores de atención (N = 26) en tres de los 10 sitios de estudio. Los temas derivados de estas primeras entrevistas clínicas preliminares sugieren que la exposición a eventos potencialmente dañinos moralmente está asociada con amplios impactos psicológicos / conductuales, sociales y espirituales / existenciales. Los primeros hallazgos también sugieren que los resultados asociados con actos de comisión u omisión y eventos que involucran las transgresiones de otros pueden superponerse. Estos resultados se combinarán con datos derivados de otros clínicos, miembros del servicio y veteranos para generar el MIOS. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Defining and Measuring Moral Injury: Rationale, Design, and Preliminary Findings from the Moral Injury Outcome Scale Consortium Traditional Chinese 標題: 介定與測量道德創傷:從道德創傷量表組織所得的邏輯依據、設計、初期發現 撮要: 本文首先描述一個國際研究組織「道德創傷量表(Moral Injury Outcome Scale, (MIOS)) 組織」所採用的邏輯依據和方法學。道德創傷為多重面向導致的後果, 而該組織旨在為其發展出有效的測量法及驗證測量。MIOS組織由研究員及臨床治療師組成, 他們均為美國、英國、荷蘭、澳洲、加拿大的現役和退役軍人服務。我們描述組織進行的心理測量發展過程其多個階段, 透過那些階段將取得現役和退役軍人及臨床治療師的現象學數據, 繼而取得作為子範疇的影響數據, 為新的道德創傷測量法提供內容。然後, 為了示範組織在測量法發展的第一階段所採用的方法學, 我們透過於10個研究地點當中的3個地方, 與治療人士進行半結構性面談與問卷訪問(N = 26), 提供小型的子組別初步結果。初步的臨床面談得出的主題反映, 經歷潛在能導致道德創傷的事件跟廣泛的心理/行為、社會、精神/存在層面的影響有關。這些初期發現亦反映, 委托或不履行的行為可能會與涉及他人犯錯的事件重疊。這些結果未來將與從其他臨床治療師、現役及退役軍人所得的數據結合, 幫助發展MIOS。 Simplified Chinese 标题: 介定与测量道德创伤:从道德创伤量表组织所得的逻辑依据、设计、初期发现 撮要: 本文首先描述一个国际研究组织「道德创伤量表(Moral Injury Outcome Scale, (MIOS)) 组织」所采用的逻辑依据和方法学。道德创伤为多重面向导致的后果, 而该组织旨在为其发展出有效的测量法及验证测量。MIOS组织由研究员及临床治疗师组成, 他们均为美国、英国、荷兰、澳洲、加拿大的现役和退役军人服务。我们描述组织进行的心理测量发展过程其多个阶段, 透过那些阶段将取得现役和退役军人及临床治疗师的现象学数据, 继而取得作为子范畴的影响数据, 为新的道德创伤测量法提供内容。然后, 为了示范组织在测量法发展的第一阶段所采用的方法学, 我们透过于10个研究地点当中的3个地方, 与治疗人士进行半结构性面谈与问卷访问(N = 26), 提供小型的子组别初步结果。初步的临床面谈得出的主题反映, 经历潜在能导致道德创伤的事件跟广泛的心理/行为、社会、精神/存在层面的影响有关。这些初期发现亦反映, 委托或不履行的行为可能会与涉及他人犯错的事件重迭。这些结果未来将与从其他临床治疗师、现役及退役军人所得的数据结合, 帮助发展MIOS。